Marina Tsvetaeva Interpreted by Chicca Gagliardo: Expanding the Scope of Russian-Italian Literary Ties - Erika Costa (Гуманитарный вектор)
The article examines Tsvetaeva’s trace in the book “The Poet of the Air” by Italian writer Chicca Gagliardo. In the 21st century – at the present stage of Russian literary studies – the problem of dialogue between Russian writers and representatives of world literature is posed and actively studied. While the issue of Marina Tsvetaeva and the Czech Republic has been the subject of extensive research and analysis, and the study on her relationship with France has been published, the same cannot be said for Italy. The relevance of the scientifi c study is incorporating Tsvetaeva’s work into the broader intercultural and international context. The novelty of the work lies in the fact that so far in Russian and Italian literary studies the issue of spiritual dialogue between M. I. Tsvetaeva and Chicca Gagliardo has not been subject of a separate study. The novelty of this study is that neither in Russian nor Italian literary studies has there been a dedicated investigation into the spiritual dialogue between M. I. Tsvetaeva and Chicca Gagliardo. The aim of the article is to trace the presence of Tsvetaeva’s themes and motifs in Gagliardo’s book “The Poet of the Air”. The work used in this paper includes Tsvetaeva’s Collected Works, scholars’ books and articles and websites containing useful information for the research. The biographical and comparative method and the method of comparativist and intertextual analysis form the methodological basis. The results of the study show the role of the Russian poet’s personality and works in the Italian writer’s novel. Tsvetaeva’s themes and motifs in the novel are emphasised, for example the concept of soul, the motifs of the “fl ight of the soul”, insomnia, “captive spirit”, the idea of sky as an abyss and others. We suggest a hypothesis on translations of Tsvetaeva’s works into Italian that Gagliardo might have been familiar with. Gagliardo’s acquaintance with M. Rea’s translation of “Poem of the Air” and S. Vitale’s “Art in the Light of Conscience” is proved. The practical signifi cance of the research lies in the possible use of its materials in the practice of school and university special courses and special seminars on the works of Marina Tsvetaeva and the problem of ‘Russian-Italian cultural and literary ties’. The study allows us to place Marina Tsvetaeva’s work within a broader intercultural and international conception and contributes to the development of Tsvetaeva’s context from an international perspective. The article provides, in particular, a broadening of the scope of the issue “Tsvetaeva’s Reception in Italy”, whereby it can be referred not only to works of realist literature.